The legal and economic aspect of associations of agricultural producers in the selected countries of the world - Redakcja (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2020)
Książka przygotowana pod redakcją prof. UAM dr hab. Anety Suchoń ma przede wszystkim charakter prawny, ale zawiera także rozdział ekonomiczny wskazujący na praktyczny wpływ zrzeszeń producentów rolnych, przede wszystkim spółdzielni producentów rolnych na rozwój gospodarki rolno-spożywczej. Autorami rozdziałów książki są pracownicy naukowi z wielu uniwersytetów w Europie, a także z Argentyny. Zmiany społeczno-gospodarcze, globalizacja, zapewnienie bezpieczeństwa żywości i żywnościowego, zmiany klimatyczne, degradacja środowiska, i kwestie dotyczące COVID 19 powodują, że zagadnienie zrzeszania się producentów rolnych na świecie jest coraz bardziej istotne. Gospodarstwo rolne niezależnie od jego wielkości jest bowiem małą jednostką i konieczna jest współpraca producentów rolnych na różnych etapach prowadzonej działalności rolniczej. Rozważania zawarte w niniejszej publikacji koncentrują się przede wszystkim na spółdzielniach w rolnictwie, organizacjach i grupach producentów rolnych oraz innych formach zrzeszania producentów rolnych występujących w Argentynie, Hiszpanii, Francji, Niemczech, Włoszech, Polsce, Słowenii i na Słowacji, a także innych wybranych krajach świata. Książka odwołuje się również do prawodawstwa Unii Europejskiej, które promuje współpracę producentów rolnych. The book edited by prof. UAM dr hab. Aneta Suchoń is mostly of a legal character. There is, however, a part on economic issues that highlights the practical influence of associations of agricultural producers, especially agricultural co-operatives, on the development of the agri-food industry. The chapters of the book have been written by scientists from universities in Argentina and Europe. Social and economic changes, globalisation, ensuring food security and safety, climate changes, environmental degradation, as well as the issues connected with the COVID-19 pandemic, are making the collaboration of agricultural producers in the world increase in importance. An agricultural farm, irrespective of its size, is a small unit on the agricultural market and it is necessary for agricultural producers to collaborate at different stages of agricultural activity. The issues raised in this publication focus mainly on the legal aspects of the activity conducted by co-operatives in the agri-food industry, by groups and agricultural producers organisations, and by other legal forms of agricultural producers associations in Argentina, France, Germany, Italy, Poland, Slovakia, Slovenia, and Spain, as well as in some other countries in the world. The book also refers to EU legislation that promotes collaboration among agricultural producers.
Keywords: zrzeszanie się producentów rolnych; organizacje producentów rolnych; spółdzielnie rolnicze; rynki rolne; Wspólna Polityka Rolna; sektor rolno-spożywczy; associations of agricultural producers; agricultural producer organisations; agricultural co-operatives; agricultural markets; Common Agricultural Policy; agri-food sector